Alloplastic Temporomandibular Joint Replacement in Ankylosing Spondylitis – Report of a case with review of literature. Issue 6 (November 2020) - Chowdhury, Sanjay Kumar Roy; Shadamarshan R, Arunkumar; Krishnaprabhu, Rajkumar; Rana, Ravinder Pal Singh
Abstract: Ankylosing spondylitis (AS) causes inflammation and ankylosis of joints lined by fibrocartilage with more predilection towards the axial skeleton, less commonly involving peripheral joints. Temporomandibular joint (TMJ) involvement in this disease is consistent with any systemic inflammatory arthropathy but in rare cases present with bony ankylosis. A case of bilateral TMJ ankylosis managed with stock alloplastic total joint replacement (ATJR) is reported. Literature review on the use of ATJR in this condition for TMJ reconstruction is also presented. The presented case is the first reported case of bilateral TMJ ankylosis managed with stock ATJR in literature and the first of its kind in India. Several problems were encountered perioperatively in this patient including difficulty in patient positioning and endotracheal intubation, restrictive lung disease due to AS, associated Inflammatory bowel disease. The methods to manage the difficulties and their clinical implications are also discussed.